Implementing Unfinished Story to Build Students’ Creative Writing - Melvita, Sirvy Mega (English Education Department STKIP Agama Hindu Singaraja, 2023)
This paper aims to explain the use of unfinished story and how it can help students to build their creative writing in the EFL context. This paper is descriptive library research. The data were collected by analyzing articles, journals, and papers. There are many ways or strategies that can be used by teachers to help students to build their creativity in writing. However, unfinished story is chosen by the teacher to create a different learning style. In addition, using unfinished story is considered a simple and effective teaching writing strategy in EFL classes. It is useful for students to build their creativity in writing where they are provided a chance to solve a problem through expressing their ideas and imagination without any fear of being judged. Additionally, in its implementation, the story given is unfamiliar to students so that they can end their own story.